Evaluation of the composition and oxidative status of omega-3 fatty acid supplements on the Finnish market using NMR and SPME-GC–MS in comparison with conventional methods - Damerau Annelie; Ahonen Eija; Kortesniemi Maaria; Puganen Anna; Tarvainen Marko; Linderborg Kaisa M. (Elsevier BV, 2022)
Previous studies disagree on the oxidative status of omega-3 supplements. The great deviation raises concerns about quality and the methods used to monitor it. This study investigated 49 omega-3 products for their fatty acid content, lipid class and oxidative status using official methods, gas and liquid chromatography with mass spectrometry and nuclear magnetic resonance spectroscopy. With minor deviations, omega-3 fatty acid content and lipid class of all products were as declared. 24% of studied products exceeded thresholds set by The Global Organization for EPA and DHA Omega-3s for peroxide and/or p-anisidine value suggesting a compromised oxidative status. However, peroxide and/or p-anisidine value were only suitable for detection of lipid oxidation in 90% or 73%, respectively, of the products. Analysis of volatile oxidation compounds can be an alternative method for p-anisidine value. Nuclear magnetic resonance spectroscopy was shown to be a rapid method for determination of oil type and lipid class.